Violation of renal transport of sodium ions under conditions of skeletal trauma of different sevsrity, complicated by blood loss - V. V. Kovalov; D. V. Popovych; A. M. Servatovych (Kazimierz Wielki University, 2019)
Objective: to find out the features of renal transport of sodium ions in the early period after skeletal trauma of different severity, complicated by blood loss. Materials and methods: In experiments was used 60 non-linear white rats, 180-200 grams weight, which were on a standard vivarium diet. All animals were divided into four groups: control (6 animals) and three experimental (in all experimental groups 18 animals). The control group included the rats that were taken just to anesthesia (thiopental sodium, 40 mg per 1 kg). In the first experimental group, under the conditions of thiopental-sodium anesthesia (40 mg per 1 kg body weight intraperitoneally), a moderate severity of closed trauma was modeled and caused a closed fracture of the femoral bones. In the second experimental group was modeled blood loss of 20-22% volumes of circulating blood with the introduction of autoblood into the abdominal cavity at a rate of 0.5 ml per 100 g of animal weight. In the third experimental group, additionally, the adjacent thigh was broken. After 1, 3 and 7 days in experimental animals, the functional status of the kidneys was determined by the method of water loading. Diuresis was determined. After two hours of urine sampling the animals, in conditions of thiopental-sodium anesthesia (80 mg per 1 kg of body weight intraperitoneally), were taken out from the experiment. In urine and blood serum, concentration of sodium ions was determined. Proximal and distal transport of sodium ions and its excretion with urine were calculated. Results and their discussion. It has been established that isolated skeletal trauma (thigh fracture) in the period of early manifestations of traumatic disease (up to 7 days) is accompanied by a significant decrease in proximal and distal transport of sodium ions, which leads to a significant increase in their excretion with urine. Additional modeling of blood loss on the background of isolated skeletal trauma has deepened the revealed violations. The proximal and distal transport of sodium ions further decreased, reaching the maximum of disturbances in 3 days. This fact indicates a certain sensitivity of transport processes of sodium ions to hypoxia caused by blood loss. However, in the case of a fracture of the adjacent thigh (deepening of the skeletal trauma), the violation of the investigated processes became even more pronounced. Violation of proximal transport of sodium ions reached a maximum after 7 days, distal - after 3 days. Violation of proximal and distal transport of sodium ions was accompanied by an increase in the excretion of sodium ions in the urine. However, during the 1 and 3 days of the post-traumatic period in all experimental groups, despite the loss of blood and the increase in the severity of skeletal trauma, the magnitude of sodium excretion was almost the same, indicating the intensive involvement of adaptive-compensatory mechanisms. An additional confirmation of this assumption is the fact that after 7 days in the case of isolated skeletal trauma, sodium excretion increases, at a time which, after simulating blood loss and fracture of the adjacent thigh, the rate remains at the previous level. Conclusion. In conditions of skeletal trauma complicated by blood loss, there is an increase in the disturbance of proximal and distal transport of sodium ions in comparison with the isolated skeletal trauma observed during the acute period of traumatic diseases (1 day of the post-traumatic period) and in the period of early manifestations (3-7 days). Under these conditions, the excretion of sodium ions in the urine increases, which is stable during the experiment and does not depend on the severity of skeletal trauma and additional blood loss.